Shear Performance of Vertical Joints in Wind Turbine Concrete Towers with Different Interface Processes - Yang Zhou; Ertong Hao; Yudong Ran; Hai Cao; Yane Li; Jike Tan (Buildings)
As a weak part of the concrete tower in wind turbines, the insufficient shear capacity of vertical joints can cause the local shear failure of the tower, reduce the overall bearing capacity and stability of the tower, and lead to safety issues. At present, the splicing of tower vertical joints mainly uses epoxy resin filling and arc bolt connections. However, sometimes the concrete near the vertical joints is damaged due to compression after applying pretension to the arc bolts, which will affect the bearing capacity and stability of the entire tower structure. If other interface processes are used for vertical joint splicing, the shear performance will be directly affected. Therefore, in order to study the influence of different interface processes on the shear performance of vertical joints in concrete tower tubes, four vertical joint specimens were designed for a pull-out test under shear load and the failure mode of the specimens and the shear capacity of the vertical joint interface were analyzed and studied. The results showed that with an increase in epoxy thickness and the application of an interface chiseling treatment, as well as injecting epoxy resin into the channels, the shear performance of vertical joints could be enhanced. Finally, based on existing research and standardized design methods, the shear capacity of vertical joints in wind turbine concrete towers was predicted, which showed that the existing design methods were not yet fully applicable to the shear capacity design of vertical joints in wind turbine concrete towers with different interface processes. Further research is needed to supplement and improve them.